Carmen Jones - Bizet, Georges 1838-1875; Preminger, Otto (Carlyle Productions, released by Twentieth Century-Fox Film Corp., 1954)
An adaptation of the tragic opera Carmen into a modern American Negro musical drama. A sensuous southern factory girl deserts a young soldier after luring him away from his sweetheart, for an arrogant prize fighter.